2019
DOI: 10.1002/hed.25606
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric vs composite flaps for mandible reconstruction

Abstract: Background Composite mandibular reconstruction requires multiple tissue components inset in different planes. Intrinsic chimeric flap design provides this, and may be best suited for these reconstructions. Methods A retrospective review of mandible reconstructions with composite, intrinsic chimeric, or 2 free flaps was performed. Patient and flap characteristics and complications were analyzed. Results Seventy‐five patients were reviewed. Defects reconstructed with intrinsic chimeric flaps had significantly mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
1
5
0
2
Order By: Relevance
“…Above all, close monitoring during the first 24-48 h after surgery remains the most critical time window for identifying an impending flap failure [46][47][48], and we found an overall postoperative complication rate of 55.2%, similarly to those percentages reported for chimeric (51%) and composite (60%) flaps use for complex oro-mandibular defect reconstruction [42], and to other rates cited previously, ranging from 48% to 71% [49,50]. The vast majority of the recorded complications had an early postoperative onset (89.3%), but only 62 out the 491 patients (12.6%) required a microsurgical revision against the 19% and 17% of re-intervention incidence for chimeric and composite flaps, respectively, according to Silva AK et al [42]. Above all, the wound infection was the most common postoperative complication, with an incidence of 13.8%.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Above all, close monitoring during the first 24-48 h after surgery remains the most critical time window for identifying an impending flap failure [46][47][48], and we found an overall postoperative complication rate of 55.2%, similarly to those percentages reported for chimeric (51%) and composite (60%) flaps use for complex oro-mandibular defect reconstruction [42], and to other rates cited previously, ranging from 48% to 71% [49,50]. The vast majority of the recorded complications had an early postoperative onset (89.3%), but only 62 out the 491 patients (12.6%) required a microsurgical revision against the 19% and 17% of re-intervention incidence for chimeric and composite flaps, respectively, according to Silva AK et al [42]. Above all, the wound infection was the most common postoperative complication, with an incidence of 13.8%.…”
Section: Discussionsupporting
confidence: 78%
“…Concerning operative time, double free flaps might be quicker due to the theoretical possibility of a 3-team approach when compared to a chimeric flap that can be harvested after tumor resection. According to literature [23], we found a mean operative time ranging between 10 and 14.4 h, which might justify to privilege double flaps reconstruction, against chimeric or composite ones for which some authors reported a mean operative time of 17 and 14 h, respectively [42]. Another possible argument against using the intrinsic chimeric flap is a steep learning curve, where flap elevation and inset require a higher level of expertise, and strong microsurgical knowledge.…”
Section: Discussionmentioning
confidence: 89%
“…15 Tabel 1. Pilihan sumber donor chimeric flap untuk rekonstruksi defek oromandibula 16,17,19,20,21 Sumber flap lain untuk rekonstruksi maksila atau mandibula adalah bagian lateral dari batas skapula dengan pembuluh darah arteri sirkumfleksa skapularis. Dalam sistem subskapular, arteri subskapular bercabang menjadi 2 cabang utama, yaitu arteri thorakodorsal dan arteri sirkumfleksa skapularis.…”
Section: Rekonstruksi Oromandibulaunclassified
“…Jaringan yang terlibat dalam rekonstruksi ini adalah krista iliaka (dari cabang asenden arteri femoralis sirkumfleksa lateral), flap kulit bagian proksimal untuk rekonstruksi bagian dalam, otot rektus femoris untuk mengisi dead space, serta flap kulit bagian distal untuk mengganti jaringan kulit luar. 19 Walaupun cukup sering digunakan dalam rekonstruksi defek mandibula, namun kualitas dari tulang radius dianggap kurang sesuai untuk rekonstruksi defek mandibula karena tingginya angka fraktur dan ketersediaan tulang yang terbatas. Namun sebaliknya, kualitas dari flap kulit yang tersedia dari region forearm dianggap yang paling baik dibandingkan flap kulit dari alternatif donor lainnya karena tipis dan lunak, sehingga cocok untuk rekonstruksi defek mukosa intraoral.…”
Section: Rekonstruksi Oromandibulaunclassified
“…Aesthetic restoration is highly desirable [ 4 ]. Autologous bone transplantation is the choice of surgical treatment in clinical practice [ 5 ]. Free flap transplantation is frequently used in mandibular reconstruction, especially for continuity defect resulting in a loss of mandibular unity.…”
Section: Introductionmentioning
confidence: 99%